1984
DOI: 10.1037/0022-3514.47.2.253
|View full text |Cite
|
Sign up to set email alerts
|

Processing time and the recall of inconsistent and consistent behaviors of individuals and groups.

Abstract: Although most researchers who have investigated the effect of expectancy on memory for behavioral information have found a recall superiority for schema-inconsistent information, this finding appears to occur most clearly only when an individual, rather than individuals in a group, is seen as performing the behaviors. In this study we demonstrate first that the individual-group distinction is important in obtaining a recall superiority of schema-inconsistent behaviors. We then investigate a mechanism hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

15
103
1
1

Year Published

1989
1989
2006
2006

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(120 citation statements)
references
References 11 publications
15
103
1
1
Order By: Relevance
“…As we noted earlier, Stern et al (1984) found that the increased processing of inconsistent information does not occur when forming impressions of a group based on information about group members' behaviors. In Experiment 2, we investigated whether the attribution process is less likely to be engaged for group targets as well.…”
Section: Methodsmentioning
confidence: 70%
See 3 more Smart Citations
“…As we noted earlier, Stern et al (1984) found that the increased processing of inconsistent information does not occur when forming impressions of a group based on information about group members' behaviors. In Experiment 2, we investigated whether the attribution process is less likely to be engaged for group targets as well.…”
Section: Methodsmentioning
confidence: 70%
“…Research has shown that when forming impressions of individuals, perceivers devote additional attention to processing information that is inconsistent with a prior expectancy (Bargh & Thein, 1985;Stern et al, 1984). This increased processing reflects an effort to reconcile the unexpected information with the overall impression of the target person and may entail the review of previously acquired items of information Srull, 1981) as well as attributional reasoning to explain the unexpected behaviors.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This inconsistent information serves to violate your expectations. A large body of research indicates that inconsistent or unexpected information leads to spontaneous causal thinking (see Weiner, 1985 for a review) and more effortful cognitive processing relative to consistent or expected information (e.g., Bargh & Thein, 1985;Stern, Marrs, Millar, & Cole, 1984). Behavior that disconfirms a prior expectation also prompts attempts to explain such behavior (e.g., Hastie, 1984;Pyszczynski & Greenberg, 1981).…”
mentioning
confidence: 99%